Design of TiO2@graphene nanosheets with rough surface and its reinforcement to polyarylene ether nitriles. (7th July 2015) - Huang, Xu; Wang, Kai; Jia, Kun; Liu, Xiaobo
<x xml:space="preserve">Abstract</x> The interfacial interaction is extremely important when dealing with filler‐reinforced polymer materials. Herein, in order to improve the interfacial interaction with the polyarylene ether nitriles (PEN) matrix, a three‐dimensional rough structure was designed. First, needle‐like TiO2 nanocrystals were grown on each surface of the graphene. Morphology analysis proved that rough TiO2 nanocrystals were coated on the graphene nanosheets. Then, TiO2@graphene/PEN composites were fabricated to investigate the filler–matrix interaction. Thereafter, the different polymer chains could be interlocked by the TiO2 "needles" when the rough TiO2@graphene was embedded into the polymer resin. The surrounding PEN polymer chains (work as ropes) could tie to the "needles" (work as wood pile). That is to say, the effective polymer chain length was greatly lengthened, resulting in the improvement of interfacial interactions and mechanical properties. Most importantly, the morphology, mechanical and rheological tests of the composites also proved the improvement of interfacial interactions and mechanical properties. Copyright © 2015 John Wiley & Sons, Ltd.